As night falls [large type] : a novel - Milchman, Jenny (Wheeler Publishing, 2015)
In her isolated home in the Adirondack woods, Sandy Tremont makes dinner after a fight with her daughter. Upstairs, fifteen-year-old Ivy keeps her distance from her mother. Sandy's husband, Ben, a wilderness guide, arrives late to a home simmering with unease. Nearby, two desperate men on the run make their way through the fading light, bloodstained and determined to leave no loose ends.